ANIONIC PEROXIDASE GENE POLYMORPHISM IN WHEAT - I. V. Maksimov; G. F. Burkhanova; O. I. Kuzmina; V. A. Vakhitov (Труды по прикладной ботанике, генетике и селекции, 2018)
The results postulated a close genetic proximity of the peroxidase gene AK333699 of Triticum aestivum L. among Triticum L. species. At the same time - T. compactum Host, T. durum Desf., T. macha Dekapr. & Menabde, T. spelta L., T. turgidum L., T. urartu Thum. ex Gandiljan and T. aestivum (media genomes Au) clustered to the subgenus Triticum. Species T. compactum, T. durum, T. macha, T. spelta, T. turgidum, T. urartu and T. aestivum (media genomes Ab) clustered together to the subgenus Boeoticum Migusch. et Dorof. Thus, the sequenced fragments homologous to the peroxidase gene TC151917 of T. aestivum and the similar peroxidase gene in another species can be identified as a separate cluster of polysaccharide-specific isoperoxidases which can bind on pathogens cell wall structures and initiate plant defense mechanisms.